The Influence of Admixtures Accelerating the Pine Bark Composting Process on Variation in the Bacteriological State of Composts - Starzyk Justyna; Czekała Wojciech (Archives of Environmental Protection, 2014)
The focus of the study was on the dynamics of the variation in the population of copiotrophic and oligotrophic bacteria and actinobacteria as well as the level of acid and alkaline phosphatase activities taking place during pine bark composting, depending on the application of different organic admixtures and the Effective Microorganisms microbiological preparation as well as variation in pH values and temperature. Above all, the trend in the variation in the population of microorganisms under analysis and enzymatic activity depended on the type of admixture applied to the composted pine bark. Apart from that, the course of microbiological activity was also influenced by temperature variation, which resulted from the course of the composting process. The results obtained in the experiment proved that the admixture of PGM (plant green matter) to the composted prisms had stimulating influence on the microbiological indexes under analysis.